Does nest occupancy by birds influence the microbial composition? - Xin, Jiajia; Cao, Heqin; Bao, Xiaoyang; Hu, Canshi (Frontiers in Microbiology, 2023)
Nest microbiota plays a vital role in the breeding and development of birds, which not only provides protection to bird hosts but also negatively affects the host. At present, it is unclear whether the composition of the microbes in the nests is affected by nesting. For this reason, we hung artificial nest boxes to simulate the natural nesting environment and combined 16S rRNA and ITS high-throughput sequencing technology to further study the differences in microbial composition and richness between used nests and control nests of Japanese tits (Parus minor). The study found that the bacteria in used nests and control nests showed significant differences at the phylum level (p < 0.05). It is also worth noting that the predominant bacteria in used nests were Proteobacteria (51.37%), Actinobacteria (29.72%), Bacteroidetes (6.59%), and Firmicutes (3.82%), while the predominant bacteria in control nests were Proteobacteria (93.70%), Bacteroidetes (2.33%), and Acidobacteria (2.06%). Both used nests and control nests showed similar fungi at the phylum level, which consisted mainly of Ascomycota and Basidiomycota, although significant differences were found in their relative abundance between both groups. The results of alpha diversity analysis showed significant differences in bacteria between the two groups and not in fungi. However, the beta diversity analysis showed significant differences between both bacteria and fungi. In summary, our results showed that the used nests had a higher abundance of beneficial microbiota and a lower presence of pathogenic microbiota. Therefore, we speculate that birds will change the characteristics of the nest microbial composition in the process of nest breeding to ensure their smooth reproductive development.